Design recommendations for active games - Martinez, Pamela N. (Frontiers in Digital Health, 2022)
Active gaming is a form of video gaming that requires full body motion or varying degrees of physical activity to play a game. While active gaming has regained momentum, their design and specific components of active games that make them engaging is limited. This study identifies, analyzes and categorizes specific design mechanics and features used in active games. It answers the question: Which, if any, game mechanics and features can a panel of experts in academia, health and the game industry agree on as valuable and impactful to the construction of successful and engaging active games? Using a Delphi study, nine experts answered questions related to active gaming. They reached agreement on 20 of the 21 inquiries regarding game design focused on motivation, social influences and flow. Their feedback offers recommendations on the design of future active games and identifies emerging trends. This study shares their notes and translates the findings into specific recommendations for developers on the design of active games. The field of active gaming has matured, there are pockets of experts in design, research and implementation. Active gaming has maintained continuity, however, player enthusiasm and engagement in these types of games is consistently an issue. Through better game design and newer types of active games, players interest will persist. These guidelines can inform developers working with newer technologies, such as mobile devices, enhanced game consoles, virtual and augmented reality platforms to create active games that inspire gamers to play.